Perbedaan Efektivitas Leaflet dan Poster Produk Komisi Penanggulangan AIDS Kabupaten Jember Dalam Perilaku Pencegahan HIV/AIDS - Gani, Husni Abdul; Istiaji, Erdi; Kusuma, Atdelia Irla (FKM - UNEJ, 2014)
HIV/AIDS is public health problems, one of the causes HIV/AIDS is free seks. Until now it has not been found vaccine the prevention of HIV/AIDS and in medicine to treating HIV/AIDS, the best approach with health promotion using media of health promotion in the form of leaflets and posters product AIDS Commission district Jember. This research to analyze the difference of the effectiveness of leaflet and poster product AIDS commission district Jember in the behavior of hiv/aids prevention (a case study on the faculty of non Health University Jember student Cohort 2010). This research is experiments research with quasi design experiment, The total samples was 96 students on the faculty of non Health University Jember student Cohort 2010) and the analysis of using test willcoxon signed rank test, kruskal walls, as well as the Mann Whitney Test with a significance level of 5%. the Results of the research there is a difference in the effectiveness of leaflets and posters product AIDS commission district Jember on Aids Prevention, leaflets more effective in improving knowledge, attitudes and practice of prevention of HIV/AIDS compared to media posters Keywords: Effectiveness, Leaflet, Poster, Behavior of HIV/AIDS Prevention